Evaluation of the effectiveness of lipid-lowering agents - V. G. Shevko; M. A. Galas; T. L. Galankin; A. S. Kolbin (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. Nowadays, lipid-lowering therapy is considered an essential strategy for primary and secondary prevention of cardiovascular outcomes, which is confirmed by numerous studies. Nevertheless, researches are often guided by analysis of surrogate endpoints, which becomes not just everyday practice, but also an actual problem. Surrogate endpoints are wellknown sources of bias that can distort the risk-benefit analysis.The objective of the study was to assess the significance of lipid-lowering therapy with statins in relation to mortality.Methods and materials. The analysis of prospective controlled trials was carried out with a sample of 2000 patients and more, in which mortality rate was assessed for 2 or more years of statin therapy, as well as systematic literature reviews with a meta-analysis of mortality rates. The search was carried out on websites of the Russian scientific electronic libraries eLibrary and сyberleninka , English-language works – on the PubMed website.Results. An increase in survival during treatment with statins in case of secondary prevention of cardiovascular diseases reached about 2 % after five years’ treatment and was absent after ten years’ treatment. The average increase in life expectancy was only 4.1 days. Primary prevention with statins has not been shown to increase survival significantly.Conclusion. Effectiveness of lipid-lowering therapy with statins as a part of secondary prevention of cardiovascular outcomes assessed by surrogate endpoints could be greatly exaggerated. A biased approach to selecting surrogate endpoints can lead to incorrect results. Similarly, the encouraging results of therapy with statins in the prevention of cardiovascular mortality may be biased when the effect of statins on other causes of death is not considered. Mortality refers to a universal endpoint that characterizes both the effectiveness and safety of a drug.